PERBEDAAN MINAT BELAJAR SISWA MENGGUNAKAN APLIKASI GOOGLE MEET DAN ZOOM MEETING PADA MATA PELAJARAN PAI - Nanda Kurnia Fajar; Yayat Suharyat (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2022)
The outbreak of the COVID-19 virus in Indonesia has caused activities across all sectors to undergo changes and adjustments, including in the field of education. To reduce the spread of the virus, the government established distance learning policies as a solution to the limitations of the teaching and learning process. Student learning achievement is caused by one of the internal factors, namely Learning Interests. Based on the results of the survey, the Google Meet and Zoom Meeting application became the most popular distance learning media. This can be one of the factors that can affect students' learning interests. The study was created with the aim of distinguishing students' learning interests between using the Google Meet app and Zoom Meeting on PAI subjects.This research uses comparative quantitative methods (ex post facto) by spreading questionnaires online to students of SMAN 3 Babelan as a source of research data. A total of 54 students were objected to the study. For data processing techniques, the study used descriptive statistical techniques. From the results of this study, the results of the t count are smaller than the t table, so it can be concluded that there is no significant difference in student learning interest between using the Google Meet app and Zoom Meeting on PAI subjects. From the results of this study, the results of the t count are smaller than the t table, so it can be concluded that there is no significant difference in student learning interest between using the Google Meet app and Zoom Meeting on PAI subjects.